Acoustic Emission Response Characteristics of Anthracitic Coal under Uniaxial Compression. (25th September 2020) - Wang, Haiyan; Wang, Gongda; Zhang, Guojun; Du, Feng; Ma, Ji
Abstract : The damage evolution of coal is accompanied by the generation of acoustic emission (AE) signal. Through the analysis and research of the AE response characteristics of coal deformation and failure, it is helpful to reveal the initiation, propagation, and fracture evolution of microcracks in coal. In this work, taking the anthracite coal as research object, the basic mechanical parameters of the coal samples were obtained by ultrasonic tests and uniaxial compression experiments. Meanwhile, the AE response characteristics of coal samples during uniaxial compression were obtained through AE experiments. The results show that when the density is low, the wave velocity of the coal sample decreases with the increase of density. When the density is higher than a certain value, the wave velocity of the coal sample increases with the increase of density. Through the measurement of ultrasonic wave velocity, it is found that there is some nonuniformity and anisotropy in raw coal samples. The ring counts, energy counts, and AE events with time in uniaxial compression process have approximately normal distribution. The AE events are concentrated in the elastic stage and yield stage, and the energy amplitude of AE events is higher in the plastic stage. Compared with the ring counts and energy counts, the AE events have a good positioning function, which can better reflect the evolution of internal cracks of coal samples during uniaxial compression.